The Treaty of Lausanne
XVIII, 344 p. 18 illus., 17 illus. in color.
Keywords: This book explores the creation and legacy of the Treaty of Lausanne, which marked the end of the First World War in the Near East, as well as the end of the old Eastern Question. It deals with the role, political and legal, of the Treaty in the international system, its effects on the national policies of the Great Powers and of regional States, the impact of economic issues and oil diplomacy, along with its social repercussions in the compulsory exchange of Greek and Turkish populations. The book brings together historians, political scientists, experts on international relations, and scholars of international law to cast new light on the shaping of the contemporary Eastern Mediterranean and the Middle East, and the interaction between the regional and the global. It is valuable resource for academics and practitioners focused on all these areas of study. Maria Gavouneli is Professor of International Law and Deputy Director of the Athens Public International Law Center (Athens PIL) at the Faculty of Law of the National and Kapodistrian University of Athens, Greece. She also serves as Director General of the Hellenic Foundation for European and Foreign Policy (ELIAMEP). Evanthis Hatzivassiliou is Professor of Post-war History at the Department of History and Archaeology of the National and Kapodistrian University of Athens, Greece, and the Secretary-General of the Hellenic Parliament Foundation for Parliamentarism and Democracy. His publications include NATO and Western Perceptions of the Soviet Bloc: Alliance Analysis and Reporting, 1951-1969 (2014). Panayotis Tsakonas is Professor of International Relations and Security Studies at the National and Kapodistrian University of Athens, Greece. He also serves as Head of the Programme on Security and Foreign Policy at the Hellenic Foundation for European and Foreign Policy (ELIAMEP). His publications include The Incomplete Breakthrough in Greek-Turkish Relations. Grasping Greece’s Socialization Strategy (2010).